Fitness, technology and society amusing ourselves to life - Millington, Brad (Routledge research in sport, culture and society, 2018)
The fitness industry is experiencing a new boom characterized by the proliferation of interactive and customizable technology, from exercise-themed video games to smartphone apps to wearable fitness trackers. The book explores the origins of contemporary fitness technologies, considers their implications for consumers, producers, and for society in general, and reflects on what they suggest about the future of fitness experience. Casting new light on theories of technology and the body, this is fascinating reading for all those interested in physical cultural studies, technology, and the sociology of sport.